2014
DOI: 10.1051/matecconf/20141306003
|View full text |Cite
|
Sign up to set email alerts
|

Skylight Application for Natural Lighting in a Building; the University of Tehran Branch of Melli Bank Case Study

Abstract: This study investigated the quality and potential lighting energy savings in a bank building retrofitting project in Tehran by using solar passive lighting. The retrofitting scenarios are based on OFFICE project findings. Despite the increase in occupancy and service quality of the bank after retrofitting, the peak electricity consumption significantly decreased (approximately 20%). The results showed that even the proper solar passive lighting in most of day hours had been enough to satisfy the existing build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Rezaei et al [71] had conducted a review of different glazing types, technologies, and materials, which can be a start point for further studies to evaluate their impacts on the HVAC system and lighting energy loads by using them in skylights. A case study by Nasersharifi and Assadi [72] for arid climates showed that skylights can save 20% of lighting energy loads, and the payback period can be 19.75 years [73]. Li et al conducted research in a subtropical climate by applying semi-transparent PV over the glass to improve its efficiency, but this increased its payback period to 23 years [74].…”
Section: Skylight Roofsmentioning
confidence: 99%
“…Rezaei et al [71] had conducted a review of different glazing types, technologies, and materials, which can be a start point for further studies to evaluate their impacts on the HVAC system and lighting energy loads by using them in skylights. A case study by Nasersharifi and Assadi [72] for arid climates showed that skylights can save 20% of lighting energy loads, and the payback period can be 19.75 years [73]. Li et al conducted research in a subtropical climate by applying semi-transparent PV over the glass to improve its efficiency, but this increased its payback period to 23 years [74].…”
Section: Skylight Roofsmentioning
confidence: 99%
“…Nowadays, the importance of lighting from skylights and other vertical systems is crucial, and the advantages of their application on common and irregular-shaped roof buildings are proven [15]. A recent study performed by the University of Tehran reports the outcomes of a retrofitting project based on solar passive lighting, which has allowed to reduce the energy consumptions of above 20% [16]. Other relevant and innovative contributions in the field of skylight design are reported in [17,18].…”
Section: Introductionmentioning
confidence: 99%